Understanding the hetero-aggregation mechanism among sulfide and oxide mineral particles driven by bifunctional surfactants: Intensification flotation of oxide minerals. (1st August 2021) - Liu, Sheng; Xie, Lei; Liu, Guangyi; Zhong, Hong; Zeng, Hongbo
Graphical abstract: The two-step hetero-aggregation among chalcopyrite and malachite particles sequentially-induced by HABTC's nonpolar and bipolar groups. Highlights: A bifunctional surfactant HABTC aggregated chalcopyrite and malachite particles. HABTC's hydrophobic force notably increased the "jump in" attachment distance. To bond different minerals via HABTC's bifunctional groups improved adhesion forces. Hetero-aggregation was sequentially induced by HABTC's nonpolar and bipolar groups. Hetero-aggregation realized the carrier flotation of malachite by chalcopyrite. Abstract: To promote the separation and enrichment efficiency of oxide minerals from the sulfide-oxide ores through froth flotation has become a challenging issue. In this paper, the driving role of S -[(2-hydroxyamino)-2-oxoethyl]- N, N -dibutyl-dithiocarbamate (HABTC) in facilitating the aggregation of copper sulfide and oxide minerals particles was explored through atomic force microscope (AFM) force measurements and the extended Derjaguin-Landau-Verwey-Overbeek (DLVO) theory calculation. AFM imaging, contact angle measurement and surface energy computation showed that the self-assembly of HABTC on chalcopyrite and malachite improved the hydrophobicity of their surfaces and reduced their interaction free energies. AFM force measurements observed that the "jump in" attachment occurred at 8.6 12.5 nm during the approaching chalcopyrite towards malachite in HABTC solution, which was mainly attributed to the hydrophobic interaction between them. And the adhesion force between them in HABTC solution was much larger than that in OHA solution, being contributed to HABTC's bridging role driven by its uncoordinated dithiocarbamate or hydroxamate groups to bond with the surface copper atoms of different minerals. The two-step hetero-aggregation among chalcopyrite and malachite particles sequentially-induced by HABTC's nonpolar and bipolar groups built a carrier flotation platform where the floatability of malachite particles was significantly promoted by chalcopyrite particles with a superior hydrophobicity, resulting in an improved flotation recovery of malachite.